Study of Circulating Oxidative Stress Markers and Level of Antioxidant in Non-Alcoholic Fatty Liver Disease (NAFLD) (Medical Forum Monthly, 2024)
Objective: To document the markers of oxidative stress and state of endogenous and exogenous antioxidants levels in non-alcoholic fatty liver disease. Study Design: Case control study. Place and Duration of Study: This study was conducted at the Department of Medicine, Services Hospital Lahore from December 2018 to May 2019. Materials and Methods: Fifty non-alcoholic fatty liver disease patients with elevated aminotransferases and presence of fatty liver on ultrasound were included in the study. Fifty healthy individuals of same age and sex matched healthy were selected as control. Patients with positive viral serology, alcohol use and known diabetics were excluded. Results: Oxidative stress determinants including malondialdehyde (5.44 nmol/ml) and nitric oxide (15.5µmol/l) levels are found to be statistically significantly raised and endogenous antioxidants including glutathione (4.91 mg/dl), catalase (1.43 mmol/mol of protein), superoxide dismutase (0.24 nmol/ml) as well as exogenous antioxidants including vitamin C (0.33 mg/dl) and vitamin E (0.22 mg/dl) were reduced significantly in nonalcoholic fatty liver disease patients. Conclusion: Non-alcoholic fatty liver disease is associated with derangement of multiple circulatory oxidative stress parameters and antioxident thus depicting a significant role of oxidative stress in disease mechanism.